Customer satisfaction of diners in selected restaurants in Silang Cavite - Dimapilis, Justin Belasa; Garcia, Lemuel Ryan Marqueses; Reyes, Mary Rose Layugan; Tabuyo, Jimford Unida (Journal of Indonesian Tourism, Hospitality and Recreation, 2025)
AbstractThis research aimed to determine whether socio-demographic characteristics influenced customer satisfaction among diners in selected restaurants in Silang, Cavite. Specifically, it examined factors such as age, gender, civil status, occupation, income level, and highest educational attainment, along with social factors like nationality, social class, dining frequency, dining companions, dining occasions, and restaurant preferences. The study explored how these variables affected customers' perceptions of food quality, service quality, price, location, ambiance, and online reviews. This study employed quantitative research design, purposive sampling from 300 respondents across 15 selected restaurants. ANOVA and independent t-tests were applied to determine significant differences in satisfaction levels based on socio-demographic variables. The results of the study indicated that customers had the highest level of satisfaction with the ambiance of the selected restaurants, as reflected in a weighted mean equivalent to the verbal interpretation of “Strongly Agree.” Furthermore, notable differences were observed in relation to civil status, income level, social class, dining frequency, dining companions, dining occasions, and restaurant preferences. Overall, this study provided empirical data that could serve as a foundation for future studies on customer behavior, service quality, and restaurant management.AbstrakPenelitian ini bertujuan untuk mengetahui apakah karakteristik sosio-demografis memengaruhi kepuasan pelanggan di antara pengunjung restoran terpilih di Silang, Cavite. Secara khusus, penelitian ini meneliti faktor-faktor seperti usia, jenis kelamin, status pernikahan, pekerjaan, tingkat pendapatan, dan pendidikan terakhir, serta faktor sosial seperti kebangsaan, kelas sosial, frekuensi makan di luar, teman makan, kesempatan makan, dan preferensi restoran. Penelitian ini menelaah bagaimana variabel-variabel tersebut memengaruhi persepsi pelanggan terhadap kualitas makanan, kualitas layanan, harga, lokasi, suasana, dan ulasan daring. Penelitian ini menggunakan desain penelitian kuantitatif dengan teknik purposive sampling terhadap 300 responden dari 15 restoran terpilih. Uji ANOVA dan t-test independen digunakan untuk menentukan perbedaan signifikan dalam tingkat kepuasan berdasarkan variabel sosio-demografis. Hasil penelitian menunjukkan bahwa pelanggan memiliki tingkat kepuasan tertinggi terhadap suasana restoran yang diteliti, dengan rata-rata tertimbang yang setara dengan interpretasi verbal “Sangat Setuju.” Selain itu, ditemukan perbedaan yang signifikan terkait status pernikahan, tingkat pendapatan, kelas sosial, frekuensi makan di luar, teman makan, kesempatan makan, dan preferensi restoran. Secara keseluruhan, penelitian ini memberikan data empiris yang dapat dijadikan dasar bagi penelitian selanjutnya mengenai perilaku pelanggan, kualitas layanan, dan manajemen restoran.